A study of GPS PPP velocity estimation with the constraints of Doppler observation. Issue 12 (15th December 2020) - Wang, Xingxing; Tu, Rui; Zhang, Rui; Han, Junqiang; Fan, Lihong; Zhang, Pengfei
Abstract: Precise Point Positioning Velocity Estimation (PPPVE) and Doppler Velocity Estimation (DVE) are two commonly used methods for precise velocity estimation with a stand-alone GPS receiver. The accuracy of PPPVE is affected by the dynamic model and the dynamic conditions of the vehicle, while the motion state of the vehicle has little influence on DVE. Therefore, we propose an approach by combining PPPVE and DVE, namely PPP-DVE. This method combines the high accuracy of PPPVE and immunity of DVE to vehicle dynamic conditions, and can provide high-precision position, velocity, and acceleration measurements simultaneously. The results show that when the vehicle is stationary or moving smoothly, the performance of PPP-DVE is the same as that of PPPVE. However, when a sudden change in the status of the vehicle occurs, such as braking, turning, accelerating, etc., the accuracy of velocity measured by the PPP-DVE with the constraints of DVE is better than that measured by PPPVE. Overall, the accuracy and reliability of velocity determination are significantly improved with use of the proposed method.